Family history of substance use disorder and parental impulsivity are differentially associated with neural responses during risky decision-making - Aloi, Joseph; Kwon, Elizabeth; Hummer, Tom A.; Crum, Kathleen I.; Shah, Nikhil; Pratt, Lauren; Aalsma, Matthew C.; Finn, Peter; Nurnberger, John; Hulvershorn, Leslie A. (Frontiers in Neuroimaging, 2023)
Background: Risky decision-making is associated with the development of substance use behaviors during adolescence. Although prior work has investigated risky decision-making in adolescents at familial high risk for developing substance use disorders (SUDs), little research has controlled for the presence of co-morbid externalizing disorders (EDs). Additionally, few studies have investigated the role of parental impulsivity in offspring neurobiology associated with risky decision-making. Methods: One-hundred twenty-five children (28 healthy controls, 47 psychiatric controls with EDs without a familial history of SUD, and 50 high-risk children with co-morbid EDs with a familial history of SUD) participated in the Balloon Analogue Risk Task while undergoing functional magnetic resonance imaging. Impulsivity for parents and children was measured using the UPPS-P Impulsive Behavior Scale. Results: We found that individuals in the psychiatric control group showed greater activation, as chances of balloon explosion increased, while making choices, relative to the healthy control and high-risk groups in the rostral anterior cingulate cortex (rACC) and lateral orbitofrontal cortex (lOFC). We also found a positive association between greater activation and parental impulsivity in these regions. However, within rACC, this relationship was moderated by group, such that there was a positive relationship between activation and parental impulsivity in the HC group, but an inverse relationship in the HR group. Conclusions: These findings suggest that there are key differences in the neurobiology underlying risky decision-making in individuals with EDs with and without a familial history of SUD.